Effects of hyperleptinemia in rat saliva composition, histology and ultrastructure of the major salivary glands. (December 2018) - Lamy, Elsa; Neves, Sandra; Ferreira, Joana; Rodrigues, Lénia; da Costa, Gonçalo; Cordeiro, Carlos; Fialho, Luísa; Lima, Mónica; Costa, Ana Rodrigues; Antunes, Célia Miguel; Lopes, Orlando; Amado, Francisco; et al.
Highlights: Leptin receptors are present in rat major salivary glands (SG). Hyperleptinemia induces decreases in saliva amylase amount. In SG acinar cells amylase activity increases under hyperleptinemia. Leptin changes SG function. Abstract: Objective: To study the effect of the satiety hormone, leptin, in saliva proteome and salivary gland histology and ultrastructure. Design: Increases in blood leptin levels were induced through mini-pump infusion in male Wistar rats, during a period of 7 days. Saliva was collected before and at the end of the experimental period, for proteomic analysis, and major salivary glands were collected, at the end, for biochemical, histological and ultrastructural analysis. Results: Immunohistochemistry revealed the presence of leptin receptors in major salivary glands. Salivary amylase levels and enzymatic activity were decreased in saliva, whereas the enzymatic activity of this protein was increased in the cytosol of parotid gland cells. Transmission electron microscopy allowed the observation of high number of electron-dense granules in cytosol of parotid acinar cells, from leptin treated animals. Conclusions: Increased levels of plasmatic leptin result in changes in saliva composition and salivary glands function. To our knowledge, this is the first study providing evidences for a potential role of leptin in salivary gland secretion and saliva composition. An understanding of how appetite/satiety factors influence saliva composition and how this composition influences food processing in mouth may be relevant in understanding ingestivebehaviour.